Association of lifestyle factors and inflammation with sarcopenic obesity: data from the PREDIMED‐Plus trial - Itziar Abete; Jadwiga Konieczna; M. Angeles Zulet; Aina M. Galmés‐Panades; Idoia Ibero‐Baraibar; Nancy Babio; Ramón Estruch; Josep Vidal; Estefanía Toledo; Cristina Razquin; Rafael Bartolomé; Andrés Díaz‐Lopez; et al. (Wiley, 2019)
Abstract Background Sarcopenia is a progressive age‐related skeletal muscle disorder associated with increased likelihood of adverse outcomes. Muscle wasting is often accompanied by an increase in body fat, leading to 'sarcopenic obesity'. The aim of the present study was to analyse the association of lifestyle variables such as diet, dietary components, physical activity (PA), body composition, and inflammatory markers, with the risk of sarcopenic obesity. Methods A cross‐sectional analysis based on baseline data from the PREDIMED‐Plus study was performed. A total of 1535 participants (48% women) with overweight/obesity (body mass index: 32.5 ± 3.3 kg/m2; age: 65.2 ± 4.9 years old) and metabolic syndrome were categorized according to sex‐specific tertiles (T) of the sarcopenic index (SI) as assessed by dual‐energy X‐ray absorptiometry scanning. Anthropometrical measurements, biochemical markers, dietary intake, and PA information were collected. Linear regression analyses were carried out to evaluate the association between variables. Results Subjects in the first SI tertile were older, less physically active, showed higher frequency of abdominal obesity and diabetes, and consumed higher saturated fat and less vitamin C than subjects from the other two tertiles (all P < 0.05). Multiple adjusted linear regression models evidenced significant positive associations across tertiles of SI with adherence to the Mediterranean dietary score (P‐trend < 0.05), PA (P‐trend < 0.0001), and the 30 s chair stand test (P‐trend < 0.0001), whereas significant negative associations were found with an inadequate vitamin C consumption (P‐trend < 0.05), visceral fat and leucocyte count (all P‐trend < 0.0001), and some white cell subtypes (neutrophils and monocytes), neutrophil‐to‐lymphocyte ratio, and platelet count (all P‐trend < 0.05). When models were additionally adjusted by potential mediators (inflammatory markers, diabetes, and waist circumference), no relevant changes were observed, only dietary variables lost significance. Conclusions Diet and PA are important regulatory mediators of systemic inflammation, which is directly involved in the sarcopenic process. A healthy dietary pattern combined with exercise is a promising strategy to limit age‐related sarcopenia.